Analisis Penerapan Akuntansi Persediaan Barang Dagangan Pada CV Vita Permai Bolawolon - Florida Noviyanti; Maria Nona Dince; Wihelmina M.Y. Jaeng (Pusat Riset dan Inovasi Nasional, 2023)
Inventory is one of the factors that play an important role in an entity can be in the form of goods available. This study aims to determine the application of merchandise inventory accounting in terms of recording, appraisal, measuring, presenting and disclosing CVs. Vita Permai, whether it is in accordance with PSAK No. 14. This type of research is qualitative descriptive research while the data collection techniques used are interviews, observations, and documentation. The informant of this study is Supervisor CV. Vita Permai, Treasurer, and Administration CV. Vita Permai. The data analysis uses informal methods of observation in which the author has determined the behavioral indicators to be observed from the data subject. The results of research on CV. Vita Permai Bolawolon is an inventory recording system used using physical methods, and FIFO (First In First Out) assessment methods. The analysis of the application of inventory accounting is not in accordance with PSAK No. 14, because based on the research that the author conducted, deficiencies were still found.